Chemical and Functional Characterization of Syzygium cumini Leaves with Antioxidant Potential (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Natural antioxidants found in plants have thus proven to be important potential therapeutic agents against oxidative damage caused by free radicals. This study evaluated the antioxidant properties and functional characteristics of the bioactive compounds in Syzygium cumini leaves via in vitro and in vivo approach. The total phenolic content (TPC: 631.43 ± 163.90 µg/mL) was found to be higher than flavonoid content (TFC: 38.05 ± 3.02 µg/mL). Based on the IC50 values, ethanolic fraction was shown to be most effective in quenching electron pairs of DPPH radicals (IC50: 0.02 ± 0.004 µg/mL), higher than methanolic extract (IC50 = 1.49 ± 0.90 µg/mL) and other fractions. The total antioxidant potential was also high in ethanolic fraction (1327 ± 5.89 µg/mL). Similarly, in vivo studies in type 2 diabetic rat model showed a reduction in the activity of catalase and a subsequent increase in malondialdehyde (MDA) content. However, S. cumini treatment abolished this antioxidant imbalance in a dose-dependent manner. The 1000 mg/kg dose resulted in a 27.28 ± 2.82 kU increase in catalase activity and a 0.67 ± 0.02 nmol/mg reduction in MDA content. The FTIR spectroscopy revealed strong O-H stretching peaks around 3260 cm⁻¹ typical for phenolic compounds. Additionally, peaks were observed for C=O, C-O, and N-H bonds. Interestingly, GC-MS profiling further confirmed the presence of strong antioxidant phenolic compounds such as catechol, 1,2,3-benzenetriol, and 3,4,5-trihydroxybenzoic acid methyl ester. Besides this, moderate levels of antioxidants with lipid solubility were also found. Derivatives of linoleic acid, oleic acid, and octadecadienoic acid belonged to this group. This indicates a combination of hydrophilic radical scavenging capacity.
Keywords: Syzygium cumini; Antioxidant activity; Phenolic compounds; GC-MS profiling; Oxidative stress